Application of Micro/Nanofabrication Techniques to On‐Chip Molecular Electronics. Issue 3 (23rd February 2021) - Lu, Zhixing; Zheng, Jueting; Shi, Jie; Zeng, Biao‐Feng; Yang, Yang; Hong, Wenjing; Tian, Zhong‐Qun
Abstract: Molecular electronics is a promising subject to overcome the size limitation of silicon‐based electronic devices. In the past decades, various micro/nanofabrication techniques have been developed for constructing molecular junctions, and a number of breakthroughs are made in the characterizations and applications of the single‐molecule device. The history and progress are reviewed in this article, laying emphasis on the recent works on the combination of micro/nanofabrication techniques with other techniques such as electrochemical deposition and surface‐enhanced Raman spectroscopy (SERS). Some prototypical single‐molecule devices such as molecular transistors are presented. Finally, the challenges and prospects in the fabrication of single‐molecule devices are discussed. Abstract : This review introduces the micro/nanofabrication techniques applied in the construction of molecular junctions, which greatly promotes the development of molecular electronics. Combining micro/nanofabrication techniques with else electrochemical methods or surface‐enhanced Raman spectroscopy, the physical and chemical properties have been investigated at the single‐molecule level. Furthermore, various molecular devices with tailored configurations have been realized, such as molecular switches and transistors.